Mitochondrial (Dys)function and Insulin Resistance: From Pathophysiological Molecular Mechanisms to the Impact of Diet - Sergi, Domenico; Naumovski, Nenad; Heilbronn, Leonie Kaye; Abeywardena, Mahinda; O’Callaghan, Nathan; Lionetti, Lillà; Luscombe-Marsh, Natalie (Frontiers in Physiology, 2019)
Mitochondrial dysfunction has been implicated in the pathogenesis of insulin resistance, the hallmark of type 2 diabetes mellitus (T2DM). However, the cause-effect relationship remains to be fully elucidated. Compelling evidence suggest that boosting mitochondrial function may represent a valuable therapeutic tool to improve insulin sensitivity. Mitochondria are highly dynamic organelles which adapt to short- and long-term metabolic perturbations by undergoing fusion and fission cycles, spatial rearrangement of the electron transport chain complexes into supercomplexes as well as biogenesis governed by peroxisome proliferator-activated receptor γ co-activator 1 α (PGC 1α). However, these processes appear to be dysregulated in type 2 diabetic individuals. Herein we describe the mechanistic link between mitochondrial dysfunction and insulin resistance in skeletal muscle alongside the intracellular pathways orchestrating mitochondrial bioenergetics. We then review current evidence on nutritional tools, including fatty acids, amino acids, caloric restriction and food bioactive derivatives which may enhance insulin sensitivity by therapeutically targeting mitochondrial function and biogenesis